Yield and quality evaluation of kundi (an intermediate moisture meat) prepared from camel, beef, and chevon (2009)
Kundi is an intermediate moisture meat (IMM) product conventionally prepared from camel meat (CM). There is a dearth of information on the production as well as*the nutritional and eating qualities of kundi from other meat types. An experiment was conducted in a completely randomized design to evaluate yield, nutrient composition and sensory characteristic of kundi prepared from CM, beef and chevon. The protein content of fresh CM (22.58%) was higher (p < 0.05) than the values of 19.57 and 20.83% obtained for beef and chevon respectively. The result showed that fresh beef has at least (p < 0.05) drip loss value of (2.46%) as against 4.03 and 3.53% obtained for CM and chevon respectively. Cooking loss values were 19.30, 21.26 and 20.36% for beef, CM and chevon respectively. Beef gave the least shear force value (6.68 kg/cm3) as compared to 8.39 kg/cm3 for CM and 7.06 kg/cm3 for chevon. The product yield ranged from 33.61 to 38.93%. Kundi from each of the 3 meat types contained about three times the protein in their respective raw meat. The ash content increased from 1.50, 1.05 and 1.31% in raw beef, CM and chevon to 5.80, 4.37 and 4.40% in kundi from corresponding meat type. Kundi from chevon was rated highest (p < 0.05) for flavour juiciness and tenderness while beef kundi (BK) was rated highest (p < 0.05) for colour. Camel kundi (CK) was rated least by the panelist in virtually all parameters scored. . The possibility of producing Kundi from beef and chevon will increase the consumption of the product especially by majority of consumers with aversion to camel meat.